Specialized Terminology in the Video Game Industry: Neologisms and their Translation - Méndez González, Ramón (Vertimo studijos, 2019)
The video game industry is growing at a very fast pace. At present, it is the biggest entertainment industry in the world, selling even more than film and music industries. Newly-developed technologies provide video game creators with the necessary tools to develop more complex game worlds, and user interaction is more important than ever. Each one has its own terminology and complexities, which must be perfectly understood in order to deliver high-quality work. Therefore, translators must be deeply aware of how all these technologies and game worlds work. More importantly, they need to be familiar with the specialized terminology they are going to come across while working in the video game industry. This paper is part of a series of studies where a corpus of 300 games is used to analyze the terminology needs of video game translation and interpreting. Specifically, this paper focuses on the relevance of neologisms—as they are one of the basic traits that define a specialized language—and defines the type of neologisms that can be found when localizing a video game with the overall goal of proving that they are common in the video game industry.
Keywords: video games; terminology; neologism; translation; localization